Rozpatrywanie przez Sejm dokumentów sprawozdawczych z działalności konstytucyjnych organów państwowych - Berek, Maciej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
Constitutional state authorities are obliged to submit to the Sejm different types of documents describing their annual activity: reports or information. The legal basis of this obligation are provisions of the Constitution of Republic of Poland or provisions of relevant acts. According to the Standing Orders of the Sejm, Sejm may examine these documents and adopt (reject) them or is only entitled to be informed (with no voting on document). Author of the article analyses legal basis of the obligation on the background of constitutional rule of balance of public authorities and controlling role of the Sejm. The subject of critical analyse is also coherence of procedure of parliamentary work on these two types of documents.
Keywords: report on activity of constitutional state authority; information on activity of constitutional state authority; rule of balance of public authorities; controlling role of the Sejm